Critique and suggested modifications of the degree days methodology to enable long‐term electricity consumption assessments: a case study in Birmingham, UK. (5th November 2015) - Azevedo, Juliana Antunes; Chapman, Lee; Muller, Catherine L.
ABSTRACT: Energy consumption and outdoor ambient temperatures are inherently related. Low temperatures increase consumption via space heating, whereas high temperatures result in increased demand for refrigeration and air conditioning. A common approach used for investigating this relationship in detail is via the calculation of heating and cooling degree days. Starting with a critical review of studies in the scientific literature that have used this technique, this study highlights a range of limitations with the methodology, particularly with respect to standardization, which potentially hinder the utility of the technique in climate change risk assessments. Using an analysis of electricity consumption in Birmingham, UK, as an example, this study calls for a standardization of the approach via the use of a universal base temperature calculated using average outdoor air temperatures. Adoption of this measure will not only enable meaningful comparisons to be made across regions, but will also permit a more robust means to account for acclimatization in longer term analyses such as that required by climate change risk assessments. This is demonstrated in this study by coupling the existing degree days methodology with a temporal analogue.